Effect of Sidewalk Design and Obstructions on Pedestrian Mobility: A Case Study of the Main Streets of Mekelle City, Northern Ethiopia - Dmtsu Gebremariam; Taamrat Kuhilen; Hanna Seboka; Berhane Grum (Advances in Civil Engineering)
Walking is the cheapest and most flexible eco-friendly mode of transport. Streets in developing countries are poorly designed and managed, and hence, there is no space or it is inadequate for walking. This study assessed the impact of narrow sidewalk designs and obstructions on safety and accessibility of pedestrians in the main streets of Mekelle city, northern Ethiopia. It also evaluated the effects of sidewalk obstructions on pedestrian level of service (PLOS). Primary data, such as road width, sidewalk space utilization, pedestrian flow, and pedestrian speed, were collected on the study main streets. Effective sidewalk width and pedestrian unit flow rate were used to evaluate the effectiveness of existing sidewalk facilities. Moreover, static obstruction management of streets was evaluated, and a minimum sidewalk width was proposed. This study revealed that sidewalk widths for most streets in Mekelle city were found below the minimum required width for mixed use areas. Besides, the average effective sidewalk width was found to be lower than the bare minimum width of 1.2 m required for two pedestrians pass each other. As a result, some of the streets in Mekelle are operating at low PLOS (E and F). Most sidewalks were designed below the minimum standard width, and they are poorly managed forcing about 25% of pedestrians to share with motorized traffic in some streets. To improve the performance of sidewalks in the main streets of Mekelle city, the minimum sidewalk width should be 4.0 m and needs to be constructed with proper zoning. Moreover, center placement of static obstructions should be avoided in narrow sidewalks. Placement of utility poles within or at the edge of frontage zone and trees at the furniture zone improves the existing effective sidewalk width by 73%. This study underlines that urban planners and designers should give emphasis to width sufficiency of sidewalks for safe mobility of pedestrians of all groups and to accommodate other road side activities.